Pengaruh Iklan Terhadap Prilaku Pembelian Konsumen Teh dalam Keluarga - Dadang Surjadi; Nana Subarna; A. lmron Rosyadi; Nurul Awalina (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2002)
EnglishThe research is aimed to study the effects of television advertising on the consumer behavior. The research uses survey method. The object of research is household. The survey activites conducted in consumer's and producer's area, which are selected purposively. The research sample for each area is distinguished stratified random sampling based on rural-urban areas. To analyse data, the research uses Chi-Square statistical method. The result of research are, television is an effective media as a tool of promotion to convey tea product information, the urban consumers are significantly reacted to response tea advertising from television. The advertising presentation of tea product on television with the low frequency (<34 times/month) can significantly affect the response of urban consumers to consume that product. The consumers group proportion which has an interest or not is not significantly different with the consumer group proportion which is response or not; The consumers group proportion which is response the tea advertised is significantly be in urban area, and which is not response is be in rural area; It is expected, the consumer reaction to response advertising is effected by family income and tea subtitution capacity; The families are reference for getting tea product information of 20% consumer, and 9% family consumers obtain the information of augmented product. To support the effectiveness of advertising on the television need to be formulated the benefit of family reference, personal selling, health benefit and tea comfort of well tea boiling, and to emphasise for creating of consumers perception with frequency.IndonesianPenelitian ini bertujuan mempelajari pengaruh iklan televisi terhadap perilaku konsumen. Penelitian menggunakan metode survei. Objek penelitian digunakan ibu rumah tangga. Penelitian dilakukan di daerah produsen dan daerah konsumen yang dipilih secara purposive. Contoh penelitian dipilih dengan metode stratified random sampling menurut strata desa-urban. Metode analisis data menggunakan analisis Chi-Square. Hasil penelitian menyimpulkan; Televisi merupakan media yang efektif untuk mengiklankan produk teh. Konsumen di daerah urban bereaksi sangat nyata dalam merespon iklan teh dari televisi. Penayangan iklan teh dalam televisi dengan frekuensi rendah (<34 kali/bulan) secara nyata dapat mempengaruhi konsumen di daerah urban. Proporsi kelompok konsumen tidak berbeda nyata antara yang menyatakan minat-tidak minat dengan yang merespon-tidak merespon teh sesuai iklan; proporsi konsumen yang merespon teh sesuai iklan secara nyata berada di daerah urban, sedangkan yang tidak merespon berada di daerah rural. Reaksi konsumen dalam merespon teh sesuai iklan televisi diduga dipengaruhi oleh pendapatan keluarga dan daya subtstitusi teh. Keluarga dan kerabat merupakan sumber referensi bagi 20% konsumen, dan 9% berasal dari penyajian di tempat penjualan. Untuk meningkatkan efektivitas iklan teh dalam televisi perlu dipertimbangkan antara lain; memanfaatkan referensi keluarga, personal selling, manfaat kesehatan dan kenikmatan seduhan teh (frekuensi dan gr/cup), pembentukan persepsi diutamakan dibanding frekuensi penayangan.